The Effectiveness of Combining Block-Based Coding with Unplugged Activities for Learning Programming Concepts in Primary Grades - Prasetyo, Bagus Dwi; Pramono, Suwito Eko; Mulyono, Sungkowo Edy (Universitas Negeri Semarang, 2024)
This research study investigates the effectiveness of an integrated approach to teaching programming concepts to primary grade students, combining block-based coding exercises (BBCEs) with unplugged activities. The backdrop is the 21st-century digital era, where computational thinking and programming have become critical skills for young learners. The research was conducted with two fourth-grade classes: one received traditional BBCEs instruction (control group), and the other combined this with unplugged activities (intervention group). A post-test was used to compare the groups' performance. The results showed that the intervention group, who experienced the blended learning approach, performed better than the control group, indicating the potential benefits of the combined approach. It's important to note that the study utilized a quasi-experimental design with intact classes and a post-test-only design, which could influence the findings. Despite these limitations, the findings contribute to the growing research on effective pedagogical approaches for teaching programming concepts, suggesting that integrating unplugged activities with BBCEs can enhance student learning outcomes.